From Local Agenda 21 to a localized Agenda 2030 – the Portuguese and Brazilian cases in perspective. Issue 3 (27th May 2019) - Guerra, João; Schmidt, Luísa; Lourenço, Luiz Brito
ABSTRACT: This article evaluates the previous experiences of Local Agenda 21 (LA21) in Portugal and Brazil, in order to identify factors hindering implementation and how its legacy might contribute to a localized Agenda 2030. Grounded on comparative analysis of LA21 applied research, it includes questionnaire surveys and a review of reports and action plans, in addition to statements collected from informal interviews with national authorities. LA21 outcomes seem to have been adversely affected by structural constraints arising from economic difficulties, and more specifically from inherited centralist traditions of local governance. Despite the fact that aspects such as community engagement in decision-making and the safeguarding of the local commons have been on the LA21 agenda ever since the Earth Summit (1992), our results show that actual achievements in these areas are meager. Nevertheless, LA21 planted the seeds of participative, bottom-up, and transformative development in local communities.